Trends in oral cancer rates in Isfahan, Iran during 1991-2010 - Sayed Mohammad Razavi; Sara Siadat; Pegah Rahbar; Sayed Mohsen Hosseini; Amir Mansour Shirani (Wolters Kluwer Medknow Publications, 2012)
Background: There is a variation in trends of oral cancers all over the world. Many investigations have reported evidence of an increasing incidence in oral cancers during recent years. The purpose of this study was to investigate time trend and changes in demographic distribution of oral cancers incidence in Isfahan during 1991-2010. Materials and Methods: In this retrospective analytic study archive of Oral Pathology Department of School of Dentistry, Isfahan University of Medical Sciences from 1991 to 2010 were reviewed. A total of 231 Pathology reports were analyzed. Age, sex, primary site, histologic type of cancer, and the referral year were recorded. Data were analyzed by using Jointpoint Regression Program 3 and SPSS 18. P value less than 0.05 consider as significant level. Results: Out of all malignancies, 55% were male and 45% were female. The most frequent cancer was squamous cell carcinoma. Comparing the two time intervals (1991-2000) and (2001-2010) showed that the ratio of carcinomas and salivary gland tumors had decreased while there was an increase in incidence of sarcomas and lymphomas. Among young persons, the occurrence of oral carcinomas (mostly SCC) is rare but sarcomas were more common in younger patients. Gingiva was the most frequently involved in oral cancers with (46%), followed by tongue with (18%). Conclusion : According to this study it revealed that some changes in trends of oral cancer have happened in Isfahan that calls for more study and evaluation of etiologies of these changes.